Movement Pattern Learning Video Heian Shodan for Beginners Extracuricular Karate Students - Reno Renaldi Putra; Agus Hariyanto; Abdul Rachman Syah Tuasikal (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Movement theory is The Heian Shodan kata designed for karate extracurricular beginners in Sidoarjo district. There are six movement patterns of the Heian Shodan Kata designed by the researcher with one movement pattern consisting of 6-13 basic karate movements in the Heian Shodan Kata. To improve skills and reduce boredom in the process of karate extracurricular activities, namely the provision of Heian Shodan kata which are packaged in the form of learning videos and study guide books. This study aims to help karate extracurricular students accelerate mastering the Heian Shodan Kata Pattern. This research uses a development research method which is often called R&D (Research and Development). Small group trials were conducted in one school in Sidoarjo district, while large group trials were conducted in three schools in Sidoarjo district. learning video products Heian Shodan Kata and study guide books as supports.